Crafty Hut - Mata, Lesley James; Jonas, Jennifer Rochelle; Sunggi, Susan Jasmine; Mohamad, Erra Farida; E. Gustin, Felizia Esther (2015)
Crafty Hut is a shop located at , Plaza Menggatal, 88450, Kota Kinabalu, Sabah that allows everyone especially women and children to have their needs satisfied in one convenient location. Crafty Hut sells bags, coin wallet, bottle holder, hat, cellphone pouch as well as other additional traditional and handmade craft. Crafty Hut is also able to provide everyone a warm and friendly environment each time they come to visit the shop. While there are many shops that also sells "handmade and traditional craft" like Crafty Hut, Crafty Hut will excel due to its uniqueness in creating and designing the craft. Through unheralded customer attention, Crafty Hut will slowly but surely gain market share as it satisfied everyone's needs and create long-term relationship. Lastly, the shop's location will allow it to attract a lot of walk in traffic since it is located near the housing area. However, people across Sabah have decided to buy our product when they want to fulfill their needs. For example, mothers decided to buy a knitted bag for their children. Crafty Hut has foreseen this opportunity to provide the finest and highest quality of product to everyone especially women and children. This has shown that Crafty Hut has the caliber to be one of the most successful handmade and traditional craft in Sabah. We, Crafty Hut, saw the opportunity that this business has the potential of success provided that it is handled efficiently. Since knitting is not that well-known in this modem lifestyle as it is in the olden days, people might find our handmade and traditional craft interesting and would want to buy the product because it is hard to find things like that nowadays. From this, Crafty Hut sees this as a way to prosper in this market, by taking advantage of all these people's needs.